MANAGEMENT OF INTERACTION WITH STAKEHOLDERS IN RUSSIAN COMPANIES - P. Shcherbachenko (Вестник университета)
The topic of management of interaction with stakeholders is gradually evolving, this indicates an increased importance of analysis and management of interaction with stakeholders. The article considers the process of managing interaction with stakeholders is considered. Effective interaction with stakeholders helps reduce non-financial risks (rehearsal, legal regulation, social labor, political, environmental and corporate governance) and identify new opportunities for the company’s development. The management process of interaction with stakeholders is based on a step-by-step analysis of all stakeholders using the matrix method and building stakeholder maps.